Problem-Based Learning for Strengthening Religious Moderation: Evidence from Tolerance Education in Islamic Higher Education - Laila Badriyah; Siti Kholidatur Rodiyah (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2026)
The rapid development of information and communication technology has increased the intensity of social interaction in diverse societies, while presenting various challenges related to intolerance, exclusivism, and social polarization. This condition shows the importance of strengthening religious moderation in the university environment through a learning process that is able to instill the values of tolerance in a more contextual manner. This study aims to analyze the effectiveness of the application of Problem-Based Learning (PBL) in increasing student tolerance as one of the indicators of religious moderation in Islamic Religious Education courses. The study uses a quantitative approach with a quasi-experimental design of the Non-Equivalent Control Group Design. The research subjects consisted of 60 first-semester students who were divided into experimental groups and control groups. Data collection was carried out using a tolerance attitude questionnaire that had been declared valid and reliable. Data were analyzed through descriptive and inferential statistics including normality, homogeneity, Paired Sample t-Test, Independent Sample t-Test, and effect size calculation using Cohen's d. The results showed that students who participated in PBL-based learning experienced a higher increase in tolerance attitudes than students who participated in conventional learning. This difference is proven to be statistically significant with an effect size value of 1.82 which is in the large category. These findings indicate that PBL is effectively used as a learning strategy to develop tolerance, strengthen reflective skills, and support the internalization of religious moderation values in students